FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MAHASISWA DALAM MEMILIH KARIR SEBAGAI KONSULTAN PAJAK - Renald Enrique Geovano Matahurila; Mira Pramudianti (CV. Denasya Smart Publisher, 2025)
This study aims to identify the characteristics that influence students' tendency to choose a career as a tax consultant. The factors analyzed include tax knowledge, job market considerations, financial rewards, and professional recognition. Data were collected through a questionnaire distributed to accounting students at Wijaya Kusuma University, Surabaya. The sample consisted of 58 respondents. This study employs multiple regression analysis using SPSS software version 20. The results indicate that the factors examined, such as tax knowledge and professional recognition, significantly influence the choice of a career as a tax consultant, while job market considerations and financial rewards do not significantly influence the choice of a career as a tax consultant.